Dual opposing actions of STW 5 on TRP receptors mediate neuronal desensitisation in vitro - Khalil, Mohammad; Zhang, Zehua; Abdel-Aziz, H.; Rabini, S.; Ammar, R. M.; Reeh, Peter; Engel, Matthias (Life Sciences, 2020)
Aims: STW 5 is an herbal drug combination used for the treatment of functional gastrointestinal disorders (FGIDs) with visceral hypersensitivity as the therapy-resistant hallmark. STW 5 has been clinically proven to alleviate visceral hypersensitivity-related symptoms, including abdominal pain, bloating, nausea, and early satiety. However, the molecular and cellular mechanisms underlying the antinociceptive action of STW 5 remain unknown. Here, we investigate the role of STW 5 in the calcium mobilisation of dorsal root ganglion (DRG) sensory neurons. Main methods: Calcium imaging experiments were performed with freshly dissociated cultured murine DRG neurons isolated from mice by microfluorometry. TRPA1-deficient DRGs, TRPV1-deficient DRGs, TRPA1/V1 double-deficient DRGs, and wild-type DRGs have been used to investigate the role of TRPs ion channels in mediating STW 5 action. Key findings: STW 5 (1.74 and 5.8 mg/ml) induced calcium ion influx into DRG neurons in a concentration-dependent manner. Calcium transients were desensitised during repeated exposure to STW 5, an effect that was facilitated in TRPA1-deficient DRGs and less pronounced in TRPV1-deficient DRGs compared to wild-type (WT) DRGs. Significance: Repeated exposure to STW 5 induced desensitisation of sensory neurons and may ultimately contribute to its proven clinical efficacy against sensory-related symptoms in patients with FGID, including abdominal pain, bloating, nausea, and early satiety. This effect is modulated by the two prominent irritant sensors in nociceptors, TRPA1 and TRPV1.
CRIS-Team Scopus Importer:2020-07-31
Keywords: Abdominal pain; Dorsal root ganglion; Functional gastrointestinal disorders; STW 5; Visceral hypersensitivity

Menthacarin induces calcium ion influx in sensory neurons, macrophages and colonic organoids of mice - Zhang, Zehua; Engel, Matthias; Koch, E.; Reeh, Peter; Khalil, Mohammad (Life Sciences, 2021)
Aims: Menthacarin is a herbal combination that is clinically used for the treatment of functional gastrointestinal disorders (FGIDs). In several clinical studies, Menthacarin reduced visceral hypersensitivity-related symptoms. Pathogenesis of visceral hypersensitivity is multifactorial. This involves several cell types and different transient receptor potential ion channels (TRPs); these ion channels are highly conductive for calcium ions. Since transient changes in cytosolic calcium levels are crucial for many functions of living cells, we investigated if Menthacarin can induce calcium influx in sensory, largely nociceptive, neurons from dorsal root ganglia (DRG), peritoneal macrophages (PMs) and colonic organoids. Main methods: We employed the calcium imaging technique on sensory neurons from DRG, PMs and colonic organoids isolated from mice. All cells were superfused by Menthacarin at several concentrations (600, 1200, 1800 μg/ml) during the experiments, followed by calcium ionophor ionomycin (Iono., 1 μM) as a positive control. Key findings: Menthacarin induced concentration-dependent calcium ion influx in all investigated cell types. Furthermore, repeated applications of Menthacarin induced tachyphylaxis (desensitisation) of calcium responses in sensory neurons and colonic organoids. Significance: Menthacarin-induced calcium influx into sensory neurons, macrophages and colonic organoids is probably related to its clinical desensitising effects in patients with FGIDs.
CRIS-Team Scopus Importer:2020-12-25
Keywords: Caraway oil; Menthacarin; Nociception; Peppermint oil; Visceral hypersensitivity

Neuro-Immune Networks in Gastrointestinal Disorders - Khalil, Mohammad; Zhang, Zehua; Engel, Matthias (Visceral Medicine, 2019)
Tissue homeostasis is controlled by multilateral cell interactions. Established in autoimmune diseases of the central nervous system, growing evidence shows a fundamental role of bidirectional communication between the nervous and immune systems in various gastrointestinal disorders. Primarily the primary sensory nervous system seems to play an important role in this cross talk because of its ability for transducing inflammatory signals and to convey them to the central nervous system, which in turn responds in an efferent manner (gut-brain axis vs. brain-gut axis). Moreover, sensory neurons that play a central role in pain processing immediately respond to inflammatory stimuli through releasing a myriad of immunomodulatory neuropeptides and neurotransmitters whose receptors are expressed in different immune cell populations. Thus, a better understanding of neuro-immune networks will pave the way to novel therapeutic strategies in inflammatory as well as functional gastrointestinal disorders. (C) 2019 S. Karger AG, Basel
CRIS-Team WoS Importer:2019-05-14

SCAMP3 is regulated by miR-128-3p and promotes the metastasis of hepatocellular carcinoma cells through EGFR-MAPK p38 signaling pathway - Kang, Le; Zhang, Zehua; Zhao, Ying (American Journal of Translational Research, 2021)
Purpose: To explore the regulatory mechanism of secretory carrier membrane protein 3 (SCAMP3) and miR-128-3p in hepatocellular carcinoma (HCC). Patients and methods: Cancer tissues and adjacent tissues of 52 HCC patients treated in our hospital were collected to explore the prognostic factors affecting their 3-year survival. HCC cells were purchased, the gene expression of Huh-7 and MHCC97 were adjusted by transfection, and the levels of SCAMP3, miR-128-3p, EGFR, p-EGFR, MAPK p38, p-MAPK p38, N-cadherin, vimentin, E-cadherin, cell proliferation, migration, invasion, apoptosis and epithelial-mesenchymal transition (EMT) were detected. A nude mouse model of HCC was constructed to verify the effects of transfection of mimics. Results: SCAMP3 was elevated in HCC patients and cancer tissues of HCC patients, while miR-128-3p showed opposite effects. High level SCAMP3 and low level miR-128-3p were related to poor prognosis of HCC. Both of them were correlated with excessive drinking history, N-stage, M-stage and pathological differentiation degree of HCC patients, as well as prognostic factors of HCC patients. SCAMP3 up-regulation or miR-128-3p down-regulation could promote HCC cell proliferation, migration, invasion, and transcription and protein levels of EGFR, p-EGFR, MAPK p38, p-MAPK p38, N-cadherin and vimentin, and inhibit HCC cell apoptosis and transcription and protein levels of E-cadherin. Dual luciferase reporter identified the targeting relationship between SCAMP3 and miR-128-3p. When both SCAMP3 and miR-128-3p were elevated or reduced, the biological manifestation of cells was not different from that of miR-NC transfected with unrelated sequences. Besides, miR-128-3p inhibited tumor growth in the HCC model in nude mice. Conclusion: SCAMP3 can be controlled by miR-128-3p and can mediate the EGFR-MAPK p38 signaling pathway to inhibit HCC cell metastasis, which is expected to become a promising therapeutic target for HCC.
CRIS-Team Scopus Importer:2021-01-22
Keywords: EGFR-MAPK p38; Hepatocellular carcinoma; Metastasis; MiR-128-3p; SCAMP3